Unexplained infertility patients have increased serum IL-2, IL-4, IL-6, IL-8, IL-21, TNFα, IFNγ and increased Tfh/CD4 T cell ratio: increased Tfh and IL-21 strongly correlate with presence of autoantibodies. (February 2015) - An, Li-Feng; Zhang, Xue-Hong; Sun, Xiao-Tong; Zhao, Li-Hui; Li, Sheng; Wang, Wei-Hua
<x xml:space="preserve">Abstract</x> Infertility is a disease of the reproductive system that affects millions of people globally. Reproductive failure is a major medical issue adversely affecting human health in the 21st century. Many factors contribute to infertility, including immune conditions which may lead to immune infertility (immunologic infertility). It is known that specific T helper cells (Th) and their cytokines are involved in the stages of infertility. The aim of this study is to provide a new diagnostic approach to immunologic infertility by investigating the correlation of follicular helper T cells (Tfh) and their secreted cytokines with the autoantibodies in peripheral blood samples from immunologically infertile patients. Thirty (30) patients suffering from immune infertility and 20 control subjects were selected as the sample base for this study. The levels of Tfh, 20 cytokines and 4 antibodies were evaluated for this investigation and evaluated using flow cytometry, antibody chip and ELISA technologies. It was found that, in immunologically infertile patients, Tfh cell numbers were significantly higher than those in the control group. Likewise, seven (7) serum cytokines were expressed to a greater degree in infertile patients compared to the control group. Finally, four (4) antibodies were found to be higher in immunologically infertile patients. The results show that, among patients with immunologic infertility, the levels of Tfh cells and IL-21 were increased significantly in peripheral blood samples and correlate positively with the autoantibodies. IL-12 was positively correlated with the two antibodies, while TNFα was negatively correlated with two additional antibodies. The detection and quantification of Tfh cells, IL-21, IL-12 and TNFα may provide new diagnostic indicators to screen for immunologic infertility.